2021
DOI: 10.3390/jcm10091946
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variation in Post-Void Residual Management after Urogynecologic Surgery: A Survey of Urogynecologists’ Practices

Abstract: To date there is no standardized regimen or evidence-based practical guideline concerning post-void residual (PVR) measurement after urogynecologic surgeries. This survey aimed to evaluate current practice patterns and the approach taken among urogynecologists surrounding PVR measurement. An online survey was sent to members of several urogynecologic societies assessing pre- and postoperative management of patients undergoing urogynecologic surgery. A total of 204 urogynecologists from 21 countries participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…Benefits to patients and health care provider teams from more judicious use of formal voiding trials include avoidance of overdiagnosis of urine residual without clinical benefit, higher patient satisfaction, fewer resource utilization, and shorter length of stay consistent with benefits of enhanced recovery after surgery protocols. 13,14,17,18 Our study found similar rates of postoperative urinary retention as prior published rates after pelvic reconstructive surgery. [3][4][5]12,[19][20][21][22][23] However, one reason for the difference in rates of urinary retention in our study specific to the posterior compartment surgery population compared with Book et al 8 may be that 50% of the patients in that study underwent mesh-augmented posterior colporrhaphy, which is often anchored in an apical location, where the risk of nerve pain or pelvic floor muscle spasm may be much greater.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Benefits to patients and health care provider teams from more judicious use of formal voiding trials include avoidance of overdiagnosis of urine residual without clinical benefit, higher patient satisfaction, fewer resource utilization, and shorter length of stay consistent with benefits of enhanced recovery after surgery protocols. 13,14,17,18 Our study found similar rates of postoperative urinary retention as prior published rates after pelvic reconstructive surgery. [3][4][5]12,[19][20][21][22][23] However, one reason for the difference in rates of urinary retention in our study specific to the posterior compartment surgery population compared with Book et al 8 may be that 50% of the patients in that study underwent mesh-augmented posterior colporrhaphy, which is often anchored in an apical location, where the risk of nerve pain or pelvic floor muscle spasm may be much greater.…”
Section: Discussionsupporting
confidence: 87%
“…In a survey of 169 international experts in urogynecology, 71% always assess PVR after urogynecologic surgery and 27% measured depending on the surgery. 14 The findings of our study support the practice of using such surgeon discretion to determine which patients may benefit from a more formalized voiding trial with PVR assessment based on procedure and risk. For example, Anglim et al 15 identified that placement of a midurethral sling, anterior repair, hysterectomy, and apical suspension procedures were significant risk factors for postoperative urinary retention.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The threshold for post-void residual to define urinary retention (in our protocol greater than 200 ml) was determined based on the fact that urodynamic studies show that the first urge to void occurs at around 250 ml 3 ; unfortunately there is no standard definition of postoperative urinary retention, which leads to the wide variation in standardized voiding protocols that exist. 5,24 Our study has a number of limitations. First, our patient population was small in number, from a single institution, and only consisted of patients undergoing minimally invasive hysterectomy; therefore, it may be difficult to generalize our findings to other patient populations who are undergoing laparotomy or radical surgery.…”
Section: Discussionmentioning
confidence: 97%